Islamic Solution on the Agricultural Land Leasing Problem: Case of Excessive Time Dispute - Imron Rosyadi; Fauzul Hanif Noor Athief; Darlin Rizki (Jurnal Ilmiah Al-Syir'ah, 2022)
The practice of leasing farmland does not always run smoothly. One of the obstacles that are often faced is the excess of rental time by tenant farmers because the plants have not yet entered the harvest period when the rental period ends. On the other hand, the land owner does not want to lose the profit that can be obtained from the duration of the excess lease. This study aims to find alternative solutions to disputes over lease contracts (ijarah). This research is a field research that is used to answer questions related to the process of implementing the practice of leasing agricultural land, the impact of excess rent for owners and tenants, as well as a contract model that can be a solution to conflicts over time in the practice of leasing agricultural land. The data was collected through interviews, the results of which were analyzed using descriptive methods, then conclusions were obtained through an inductive mindset. The data resource comes from Kalikotes, Klaten Regency. This study concludes that the beginning of the lease agreement does not conflict with Islamic law because it has been mutually agreed between the two parties, but at the end of the lease process there is a contract discrepancy. The land owner immediately asks the tenant for compensation for the excess time. The non-compliance with the agreement made by the tenant was caused by things that were completely unpredictable, where the lease period had expired but the rice could not be harvested. Both parties can resolve this conflict in a win-win manner by making a contractnew ijarah or changing the form of the contract at the beginning by using the number of harvests, not the tempo of the year.